2010
DOI: 10.1155/2010/170680
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Index, Dietary Glycemic Load, Blood Lipids, and Coronary Heart Disease

Abstract: Objective. To examine the associations of dietary glycemic index (GI) and dietary glycemic load (GL) with blood lipid concentrations and coronary heart disease (CHD) in nondiabetic participants in the Health Worker Cohort Study (HWCS). Materials and Methods. A cross-sectional analysis was performed, using data from adults who participated in the HWCS baseline assessment. We collected information on participants' socio-demographic conditions, dietary patterns and physical activity via self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
1
40
1
3
Order By: Relevance
“…The details of the study design and methodology and baseline characteristics of the study population have been described previously (16). Briefly, the HWCS is a cohort study focusing on lifestyle and chronic diseases.…”
Section: Methods Participants and Study Designmentioning
confidence: 99%
“…The details of the study design and methodology and baseline characteristics of the study population have been described previously (16). Briefly, the HWCS is a cohort study focusing on lifestyle and chronic diseases.…”
Section: Methods Participants and Study Designmentioning
confidence: 99%
“…22 It is important to note that the model became significant after adjusting by the amount of consumed carbohydrates, which means that the result is more affected by the quality of the carbohydrate than by its quantity.…”
Section: Glycemic Load and Metabolic Syndromementioning
confidence: 99%
“…Nevertheless, the recall method is still a better tool than the survey to assess food frequency. 22 Moreover, the pubertal development was not considered, which may influence the MS although values were adjusted by age. 28 Patients with a previous diagnosis of diabetes were excluded because they were already under nutritional treatment, which modified their GL.…”
Section: Limitationsmentioning
confidence: 99%
“…These studies showed that high glycemic index or glycemic load has adverse effects on blood lipid levels. [10][11][12] Contrarily, in another study, 13 the researcher examined the impact of low glycemic index (LGI) breakfasts on an overweight and obese individual and found no significant effect on lipid profile including triglycerides, HDL and LDL cholesterol concentration. 13 In the presence of equivocal findings, the effect of low glycemic index diet on blood lipids profile is still controversial.…”
Section: Introductionmentioning
confidence: 99%